A photocatalytic filter and its preparation method and application
By adopting a photocatalytic filter structure in which the PP base layer, nano-separator layer and PP base layer are interconnected, the problems of low recovery rate and short service life of existing photocatalytic materials are solved, and the material utilization rate and service life are improved. The extension is suitable for large-area applications such as pig farms.
Patent Information
- Application Number
- CN202311152276.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-09-07
AI Technical Summary
The existing photocatalytic materials are mainly powder-like, which have problems such as difficult to recover, low utilization, inconvenient transportation and high cost of use. They also experience a strong acid and strong alkali environment during the preparation process, which affects the life of the carrier and the application effect.
A photocatalytic filter composed of the PP base layer, nano -compartment, and PP base layer connects each other. The nano compartment chimeric nano -class magnetic iron powder and adhesion. Powder, through a specific layer of structure and material combination, improves the utilization rate and service life of photocatalytic materials.
It improves the utilization rate of photocatalytic materials and the service life of photocatalytic filters, reduces the acid -base environment impact during the preparation process, enhances the stability and convenience of materials, and is suitable for large -scale promotion and use.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic filters, and in particular relates to a photocatalytic filter and a preparation method and application thereof. Background Art
[0002] The odor concentration produced by pig farms is high, which not only harms the health of pigs, but also has a great impact on the environment. Innovations should be made in livestock and poultry breeding environmental control, greenhouse gas and ammonia odor reduction technologies, and the pig farm environment has gradually been taken seriously. Large-scale pig farms and building pens have also begun to consider deodorization designs. However, most of the existing pig farms use wet curtain washing for deodorization, which has poor treatment effects on harmful substances such as odor, ammonia and pathogens. Although a few pig farms are equipped with deodorization microbial systems to achieve the purpose of deodorization, there are problems with harsh reaction conditions and the need to be equipped with nutrient solution, which brings new problems to the farms.
[0003] Photocatalytic reaction is an emerging technology that uses photocatalytic materials to release active free radicals with strong oxidizing properties under light irradiation to degrade various large pollutant molecules into harmless small molecular pollutants. The entire reaction process is thorough and has no secondary pollution. It is widely used in the removal of pollutants such as printing and dyeing wastewater, antibiotic wastewater, volatile organic compounds, and formaldehyde. However, existing photocatalytic materials are almost all in powder form, and they have problems such as difficult recycling, low utilization rate, and inconvenient transportation in practical applications. Their cost of use is high, so that photocatalytic degradation of pollutants mostly remains at the stage of use in the laboratory. More importantly, the photocatalytic skeleton materials often experience strong acid and strong alkali environments during the preparation process, which to a certain extent affects the life of the carrier and the later application effect. Summary of the invention
[0004] At least in order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a photocatalytic filter and a preparation method and application thereof.
[0005] The present invention adopts the following technical solution.
[0006] A photocatalytic filter is formed by interconnecting a PP base layer, a nanometer barrier layer and a PP base surface layer along the thickness direction of the photocatalytic filter, wherein the nanometer barrier layer mainly includes nanometer-level magnetic iron powder and adhesive embedded in the surface of the PP base layer, and the PP base surface layer is solidified by PP melt, photocatalytic particles uniformly distributed in the PP melt and nanometer-level iron powder.
[0007] As a preferred embodiment, in the PP-based surface layer, based on weight ratio, homopolypropylene accounts for 60-80 parts, ethylene-vinyl alcohol copolymer accounts for 20-40 parts, compatibilizer accounts for 3-10 parts, photocatalytic particles account for 30-45 parts, and nano-iron powder accounts for 10-15 parts.
[0008] In order to further improve the service life of the photocatalytic filter, a plurality of PP columns penetrating the nano-interlayer are used to connect the PP base layer and the PP base surface layer together, and the diameter of the PP columns is 3 to 5 mm.
[0009] As a preferred solution, the thickness of the PP base layer is 1 to 2 mm, the thickness of the nano interlayer is 0.5 to 1 mm, and the thickness of the PP base surface layer is 1 to 3 mm.
[0010] One of the methods for preparing the aforementioned photocatalytic filter comprises the following steps:
[0011] Step 1, adding the raw material melt of the PP base layer into the filter screen mold;
[0012] Step 2, when the temperature of the raw material melt in the filter screen mold drops to 5 to 8°C above its melting point, the temperature is maintained constant, and then a layer of nano-magnetic iron powder with an adhesive is evenly spread on the surface of the raw material melt;
[0013] Step 3, pouring PP base layer melt onto the surface of nano-magnetic iron powder;
[0014] Step 4, after cooling and forming, the photocatalytic filter is obtained.
[0015] The second method for preparing the aforementioned photocatalytic filter comprises the following steps:
[0016] Step 11, placing the pre-prepared PP base layer into the filter screen mold;
[0017] Step 12, heating the filter screen mold so that the temperature of the PP base layer is between its melting point and softening point;
[0018] Step 13, evenly spreading a layer of nano-magnetic iron powder with an adhesive on the surface of the PP base layer;
[0019] Step 14, pouring the PP base layer melt onto the surface of the nano-magnetic iron powder;
[0020] Step 15, after cooling and forming, the photocatalytic filter is obtained.
[0021] The third method for preparing the photocatalytic filter comprises the following steps:
[0022] Step 21, immersing the PP base layer in nano-scale magnetic iron powder with an adhesive, so that the nano-scale magnetic iron powder is loaded on the surface of the PP base layer; wherein the surface of the PP base layer is provided with a plurality of micropores, and part of the nano-scale magnetic iron powder is embedded in the micropores;
[0023] Step 22, placing the PP base layer loaded with nano-magnetic iron powder in the filter screen mold, the front and back sides of the PP base layer are suspended, and the thickness of the suspended area is equal to the thickness of the PP base surface layer;
[0024] Step 23, pouring the PP base surface layer melt into the filter screen mold;
[0025] Step 24, after cooling and forming, the photocatalytic filter is obtained.
[0026] The above-mentioned photocatalytic filter is applied by installing the photocatalytic filter in the exhaust duct of the pig farm and / or the illuminated area in the pig farm.
[0027] Beneficial effects: The scheme of the present invention can not only greatly improve the utilization rate of photocatalytic materials in the photocatalytic filter, but also extend the service life of the photocatalytic filter. At the same time, it has the advantages of good stability and convenient transportation and use. During the preparation process of the photocatalytic filter, the raw materials of the photocatalytic filter will not experience a strong acid or alkali environment, which is conducive to fully exerting the performance of photocatalytic degradation of pollutants. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Embodiment 1: A photocatalytic filter, which is composed of a PP base layer, a nano-interlayer and a PP base surface layer connected to each other along the thickness direction of the photocatalytic filter, wherein the nano-interlayer mainly includes nano-scale magnetic iron powder (particle size 500-800nm) and an adhesive embedded in the surface of the PP base layer, and the PP base surface layer is consolidated by PP melt, photocatalytic particles uniformly distributed in the PP melt (photocatalytic particles are obtained by mixing Degussa P25 and melamine in a mass ratio of 2:5, adding 30mL of ultrapure water, and calcining at a muffle furnace at 550°C for 2h at a heating rate of 10°C / min) and nano-scale iron powder. In this embodiment, in the PP base layer, according to the weight ratio, homopolypropylene accounts for 70 parts, ethylene-vinyl alcohol copolymer accounts for 25 parts, compatibilizer (reactant of polypropylene maleic anhydride graft and ethylene-vinyl alcohol copolymer, wherein the polypropylene maleic anhydride graft accounts for 5.5wt% of the system) accounts for 4 parts, photocatalytic particles account for 35 parts, and nano-grade iron powder accounts for 12 parts. Among them, the thickness of the PP base layer is 2±0.1mm, the thickness of the nano-interlayer is 0.6±0.1mm, and the thickness of the PP base layer is 2±0.1mm.
[0030] The preparation method of the photocatalytic filter in this embodiment comprises the following steps:
[0031] Step 1, adding the raw material melt of the PP base layer into the filter screen mold;
[0032] Step 2, when the temperature of the raw material melt in the filter screen mold drops to 5 to 8°C above its melting point, the temperature is maintained constant, and then a layer of nano-magnetic iron powder with an adhesive is evenly spread on the surface of the raw material melt;
[0033] Step 3, pouring PP base layer melt onto the surface of nano-magnetic iron powder;
[0034] Step 4, after cooling and forming, the photocatalytic filter is obtained.
[0035] Embodiment 2: A photocatalytic filter, which is composed of a PP base layer, a nano-interlayer and a PP base surface layer connected to each other along the thickness direction of the photocatalytic filter, wherein the nano-interlayer mainly includes nano-scale magnetic iron powder (particle size 900-950nm) and an adhesive embedded in the surface of the PP base layer, and the PP base surface layer is consolidated by PP melt, photocatalytic particles uniformly distributed in the PP melt (photocatalytic particles are obtained by mixing Degussa P25 and melamine in a mass ratio of 2:7, adding 41mL of ultrapure water, and calcining at 550°C in a muffle furnace for 2h at a heating rate of 10°C / min) and nano-scale iron powder. In this embodiment, in the PP base layer, according to the weight ratio, homopolypropylene accounts for 60 parts, ethylene-vinyl alcohol copolymer accounts for 25 parts, compatibilizer (reactant of polypropylene maleic anhydride graft and ethylene-vinyl alcohol copolymer, wherein the polypropylene maleic anhydride graft accounts for 3.5wt% of the system) accounts for 3 parts, photocatalytic particles account for 45 parts, and nano-grade iron powder accounts for 15 parts. Among them, the thickness of the PP base layer is 1.5±0.1mm, the thickness of the nano-interlayer is 0.8±0.1mm, and the thickness of the PP base layer is 3±0.1mm.
[0036] The preparation method of the photocatalytic filter in this embodiment comprises the following steps:
[0037] Step 11, placing the pre-prepared PP base layer into the filter screen mold;
[0038] Step 12, heating the filter screen mold so that the temperature of the PP base layer is between the melting point and the softening point of the PP base layer;
[0039] Step 13, evenly spreading a layer of nano-magnetic iron powder with an adhesive on the surface of the PP base layer;
[0040] Step 14, pouring the PP base layer melt onto the surface of the nano-magnetic iron powder;
[0041] Step 15, after cooling and forming, the photocatalytic filter is obtained.
[0042] Embodiment 3: A photocatalytic filter, which is formed by connecting a PP base layer, a nano-interlayer and a PP base surface layer along the thickness direction of the photocatalytic filter, wherein the nano-interlayer mainly includes nano-scale magnetic iron powder (particle size 800-900nm) and an adhesive embedded in the surface of the PP base layer, and the PP base surface layer is formed by consolidating a PP melt, a photocatalytic material uniformly distributed in the PP melt (photocatalytic particles are obtained by mixing Degussa P25 and urea in a mass ratio of 2:9, adding 50mL of ultrapure water, and calcining at a muffle furnace at 550°C for 2h at a heating rate of 10°C / min) and nano-scale iron powder. In this embodiment, in the PP base layer, according to the weight ratio, homopolypropylene accounts for 80 parts, ethylene-vinyl alcohol copolymer accounts for 40 parts, compatibilizer (reactant of polypropylene maleic anhydride graft and ethylene-vinyl alcohol copolymer, wherein the polypropylene maleic anhydride graft accounts for 8wt% of the system) accounts for 10 parts, photocatalytic particles account for 45 parts, and nano-grade iron powder accounts for 10 parts. Among them, the thickness of the PP base layer is 1.8±0.1mm, the thickness of the nano-interlayer is 0.9±0.1mm, and the thickness of the PP base layer is 1.5±0.1mm.
[0043] The preparation method of the photocatalytic filter in this embodiment comprises the following steps:
[0044] Step 21, immersing the PP base layer in nano-scale magnetic iron powder with an adhesive, so that the nano-scale magnetic iron powder is loaded on the surface of the PP base layer; wherein the surface of the PP base layer is provided with a plurality of micropores, and part of the nano-scale magnetic iron powder is embedded in the micropores;
[0045] Step 22, placing the PP base layer loaded with nano-magnetic iron powder in the filter screen mold, the front and back sides of the PP base layer are suspended, and the thickness of the suspended area is equal to the thickness of the PP base surface layer;
[0046] Step 23, pouring the PP base surface layer melt into the filter screen mold;
[0047] Step 24, after cooling and forming, the photocatalytic filter is obtained.
[0048] Embodiment 4: A photocatalytic filter, which is formed by interconnecting a PP base layer, a nano-interlayer and a PP base surface layer along the thickness direction of the photocatalytic filter, and connecting the PP base layer and the PP base surface layer together by using a plurality of PP columns penetrating the nano-interlayer, and the diameter of the PP column is 4±0.5mm; wherein, the nano-interlayer mainly includes nano-scale magnetic iron powder (particle size 600-700nm) and an adhesive embedded in the surface of the PP base layer, and the PP base surface layer is consolidated by PP melt, photocatalytic particles uniformly distributed in the PP melt (photocatalytic particles are obtained by mixing Degussa P25 and melamine in a mass ratio of 2:2.5, adding 15mL of ultrapure water, and calcining at a heating rate of 10℃ / min at 550℃ in a muffle furnace for 2h) and nano-scale iron powder. In this embodiment, in the PP base layer, according to the weight ratio, homopolypropylene accounts for 750 parts, ethylene-vinyl alcohol copolymer accounts for 25 parts, compatibilizer (reactant of polypropylene maleic anhydride graft and ethylene-vinyl alcohol copolymer, wherein the polypropylene maleic anhydride graft accounts for 2wt% of the system) accounts for 8 parts, photocatalytic particles account for 40 parts, and nano-grade iron powder accounts for 15 parts. Among them, the thickness of the PP base layer is 1.5±0.1mm, the thickness of the nano-interlayer is 0.7±0.1mm, and the thickness of the PP base layer is 1.8±0.1mm.
[0049] Example 5: The photocatalytic filter in the above-mentioned example is installed in the exhaust duct of the pig farm and / or the illuminated area in the pig farm.
[0050] In the present invention, a photocatalytic filter with a specific structure is adopted, wherein the nanometer interlayer can not only prevent the PP base layer from being completely oxidized and ineffective, but also make the PP base surface layer more stably combined, and can also improve the activity of the photocatalytic material in the PP base surface layer. During use, after the photocatalytic filter is exposed to light, the part of the photocatalytic particles that receive the light will react with the PP material in the PP base surface layer, and react with the pollutants to treat the air. As the reaction continues, the photocatalytic particles located on the surface of the PP base surface layer will gradually fall off, and then, part of the photocatalytic particles originally located inside the PP base surface layer will be exposed to the outside, and continue to play the role of air treatment (one of the core points of its technical route is that every time the photocatalytic particles fall off and become ineffective, new photocatalytic particles continue to be exposed until the photocatalytic particles in the PP base surface layer completely fail), thereby achieving full utilization of the photocatalytic particles and greatly extending the service life of the photocatalytic filter.
[0051] In the present invention, the skeleton material required for the photocatalytic filter is widely available, the manufacturing cost is extremely low, and it is conducive to preparing single-layer or multi-layer sheet-shaped, cylindrical, and curved photocatalytic filters, which is particularly suitable for large-scale promotion and use in pig farms.
Claims
1. A method for preparing a photocatalytic filter, characterized in that the steps include: Step 1, adding the raw material melt of the PP base layer into the filter screen mold; Step 2, when the temperature of the raw material melt in the filter screen mold drops to 5-8°C above its melting point, the temperature is kept constant, and then the PP base layer is immersed in the nano-scale magnetic iron powder with an adhesive, so that the nano-scale magnetic iron powder is loaded on the surface of the PP base layer; Step 3, pouring PP base layer melt onto the surface of nano-magnetic iron powder; Step 4, cooling and forming to obtain a photocatalytic filter; The photocatalytic filter is formed by interconnecting a PP base layer, a nanometer barrier layer and a PP base surface layer along the thickness direction of the photocatalytic filter, wherein the nanometer barrier layer mainly includes nanometer-scale magnetic iron powder and adhesive embedded in the surface of the PP base layer, and the PP base surface layer is formed by consolidating a PP melt, photocatalytic particles uniformly distributed in the PP melt and nanometer-scale iron powder; in the PP base surface layer, according to the weight ratio, homopolypropylene accounts for 60-80 parts, ethylene-vinyl alcohol copolymer accounts for 20-40 parts, compatibilizer accounts for 3-10 parts, photocatalytic particles account for 30-45 parts, and nanometer-scale iron powder accounts for 10-15 parts; a plurality of PP columns penetrating the nanometer barrier layer are used to connect the PP base layer and the PP base surface layer together, and the diameter of the PP column is 3-5mm; the thickness of the PP base layer is 1-2mm, the thickness of the nanometer barrier layer is 0.5-1mm, and the thickness of the PP base surface layer is 1-3mm; Photocatalytic particles were obtained by mixing Degussa P25 and melamine at a mass ratio of 2:5, adding 30 mL of ultrapure water, and calcining at 550° C. in a muffle furnace for 2 h at a heating rate of 10° C. / min.
2. The method for preparing the photocatalytic filter according to claim 1, characterized in that: In step 2: A number of micropores are arranged on the surface of the PP base layer, and some nano-scale magnetic iron powder is embedded in the micropores; the PP base layer loaded with nano-scale magnetic iron powder is placed in a filter mold, and the front and back sides of the PP base layer are suspended, and the thickness of the suspended area is equal to the thickness of the PP base surface layer.
3. A method for preparing a photocatalytic filter, characterized in that the steps include: Step 11, placing the pre-prepared PP base layer into the filter screen mold; Step 12, heating the filter screen mold so that the temperature of the PP base layer is between its melting point and softening point; Step 13, immersing the PP base layer in nano-scale magnetic iron powder with an adhesive, so that the nano-scale magnetic iron powder is loaded on the surface of the PP base layer; Step 14, pouring the PP base layer melt onto the surface of the nano-magnetic iron powder; Step 15, cooling and molding to obtain the photocatalytic filter; The photocatalytic filter is formed by interconnecting a PP base layer, a nanometer barrier layer and a PP base surface layer along the thickness direction of the photocatalytic filter, wherein the nanometer barrier layer mainly includes nanometer-scale magnetic iron powder and adhesive embedded in the surface of the PP base layer, and the PP base surface layer is formed by consolidating a PP melt, photocatalytic particles uniformly distributed in the PP melt and nanometer-scale iron powder; in the PP base surface layer, according to the weight ratio, homopolypropylene accounts for 60-80 parts, ethylene-vinyl alcohol copolymer accounts for 20-40 parts, compatibilizer accounts for 3-10 parts, photocatalytic particles account for 30-45 parts, and nanometer-scale iron powder accounts for 10-15 parts; a plurality of PP columns penetrating the nanometer barrier layer are used to connect the PP base layer and the PP base surface layer together, and the diameter of the PP column is 3-5mm; the thickness of the PP base layer is 1-2mm, the thickness of the nanometer barrier layer is 0.5-1mm, and the thickness of the PP base surface layer is 1-3mm; Photocatalytic particles were obtained by mixing Degussa P25 and melamine at a mass ratio of 2:5, adding 30 mL of ultrapure water, and calcining at 550° C. in a muffle furnace for 2 h at a heating rate of 10° C. / min.
4. The method for preparing the photocatalytic filter according to claim 3, characterized in that: In step 13: A number of micropores are arranged on the surface of the PP base layer, and some nano-scale magnetic iron powder is embedded in the micropores; the PP base layer loaded with nano-scale magnetic iron powder is placed in a filter mold, and the front and back sides of the PP base layer are suspended, and the thickness of the suspended area is equal to the thickness of the PP base surface layer.
5. An application of a photocatalytic filter prepared by the method for preparing a photocatalytic filter according to any one of claims 1 to 4, characterized in that: The photocatalytic filter is installed in the exhaust duct of the pig farm and / or the illuminated area in the pig farm.
Citation Information
Patent Citations
Air filtration material and preparation method
CN1872382A